Bitterness in Life and Attitudes Towards Immigration - Panu Poutvaara; Max Steinhardt (Center for Economic Studies and ifo Institute (CESifo), 2015)
Integration of immigrants is a two-way process, the success of which depends both on immigrants and on natives. We provide new evidence on the determinants of individual attitudes towards immigration, using data from the 2005 and 2010 waves of the German Socio-Economic Panel. In particular, we show that bitterness in life is strongly associated with worries about immigration. This effect cannot be explained just by concerns that immigrants are competing with oneself in the labor market. Instead, it appears that people who feel that they have not got what they deserve in life oppose immigration for spiteful reasons.
Keywords: D72; F22; J61; 330; immigration; bitterness; native attitudes